Cisplatin plus paclitaxel and bevacizumab versus carboplatin plus paclitaxel and bevacizumab for the first-line treatment of metastatic or recurrent cervical cancer - İlhan, Yusuf; Tatlı, Ali Murat; Teker, Fatih; Önder, Arif Hakan; Köse, Fatih; Geredeli, Çağlayan; Karaağaç, Mustafa; Kaplan, Muhammet Ali; İnanç, Mevlüde; Göktaş Aydın, Sabin; Kargı, Ayşegül; Arak, Hacı; et al. (BMJ Publishing Group, 2022)
OBJECTIVE: Cisplatin-paclitaxel and bevacizumab is a frequently used treatment regimen for metastatic or recurrent cervical cancer, and carboplatin-paclitaxel and bevacizumab are also among the recommended regimens. In this study we aimed to evaluate the efficacy of these two regimens for the treatment of metastatic or recurrent cervical cancer. METHODS: Patients with metastatic or recurrent cervical cancer treated with cisplatin-paclitaxel and bevacizumab or carboplatin-paclitaxel and bevacizumab were retrospectively evaluated in this study. The clinical and demographic characteristics of patients in each group were evaluated. Median overall survival, progression-free survival, and response rates between the two groups were compared. RESULTS: A total of 250 patients were included. Overall, the numbers of patients with recurrent disease and metastatic disease were 159 and 91, respectively. The most common histologic subtype was squamous cell carcinoma (83.2%). The median duration of follow-up was 13.6 (range 0.5-86) months. The median progression-free survival was 10.5 (95% CI 9.0 to 11.8) months in the cisplatin-paclitaxel and bevacizumab group (group 1), and 10.8 (95%?CI 8.6 to 13.0) months in the carboplatin-paclitaxel and bevacizumab group (group 2) (HR 1.20; 95%?CI 0.88 to 1.63; p=0.25). The median overall survival was 19.1 (95%?CI 13.0 to 25.1) months in group 1 and 18.3 (95%?CI 15.3 to 21.3) months in group 2 (HR 1.28; 95%?CI 0.91 to 1.80; p=0.15). CONCLUSIONS: There is no survival difference between cisplatin or carboplatin combined with paclitaxel and bevacizumab in metastatic or recurrent cervical cancer.
Keywords: Cervical Cancer; Cisplatin; Versus Carboplatin Plus